Medical imaging and the new coronavirus: facing a disruptive threat - Figueiredo, Sérgio (2022)
In December 2019, a novel coronavirus was identified in Wuhan (China), from a cluster of patients with unexplained pneumonia and termed SARS-CoV-2, responsible for Coronavirus Disease (COVID)-19. Medical imaging modalities play an important role in the management of COVID-19 infection. Consequently, it is necessary to identify strategies and procedures for infection control in the medical imaging department. This document aims to present the standard operating procedures (SOPs) of radiology (RD) and nuclear medicine (NM) units and to provide information about the potential contribution of the medical imaging modalities in the present COVID-19 scenario. Chest Computed Tomography (CT) is considered the prime imaging tool for COVID-19 diagnosis and follow-up. Chest X-ray (CXR), with less accuracy, seems to be an important tool, in particular where mobility is an issue. Likewise, first reports have been published on the specific potential value of 18F-FDG PET (fluorodeoxyglucose) (positron emission tomography) imaging, predominantly related to incidental findings with ground-glass opacities and matched FDG uptake.